Implementasi 50 Tahun Sacrosanctum Concilium di Gereja Katolik Indonesia - Martasudjita, E. Pranawa Dhatu (Jurnal Orientasi Baru, 2014)
Liturgical renewal has been the driving force of the renewal of the entire life of the Catholic Church of the Second Vatican Council. After 50 years of the Council, the question of its implementation remains crucial and relevant. How the â€œletter and spiritâ€ of the Council have been translated and manifested into a renewed life of different ecclesial communities within the Catholic Church up to now? This study will address this question of implementation. A modest research on the liturgical renewal guided by important insights of the Sacrosanctum Concilium will be done while taking into account carefully an anniversary publication on 50 years Vatican II entitled Mozaik Gereja katolik Indonesia â€“ 50 years After Vatican II (2013) by the Pontifical Faculty of Wedabhakti, Yogyakarta. This publication presents an insider-reflection of the dioceses in Indonesia precisely on the implementation of the call of renewal of the Second Vatican Council. Subsequently, some liturgical concern will be addressed to promote a possible further renewal.